Distinctive targetable genotypes of younger patients with lung adenocarcinoma: a cBioPortal for cancer genomics data base analysis. Issue 1 (2nd January 2020) - Hou, Helei; Zhang, Chuantao; Qi, Xiaogai; Zhou, Lei; Liu, Dong; Lv, Hongying; Li, Tianjun; Sun, Dantong; Zhang, Xiaochun
ABSTRACT: There is still limited comprehensive genotyping data about young patients with lung adenocarcinoma. Herein, next generation sequencing (NGS) data of lung adenocarcinoma patients was retrospectively analyzed to evaluate the relationship between young age at diagnosis and the comprehensive molecular characteristics. The cBioPortal for Cancer Genomics database was queried for cancer genomic studies of lung adenocarcinoma and a cohort of 773 patients with complete cancer genomics data was selected from 2 of 11 studies. The relationship between age at diagnosis and frequency of targetable genotypes was analyzed and verified in another cohort composed of 177 Chinese lung adenocarcinoma patients undergoing NGS assay. Of the 773 eligible lung adenocarcinoma patients, younger age was associated with an increased likelihood of a targetable genotype ( P  < .001). Specifically, a higher prevalence of  EGFR  mutations ( P  = .005),   ALK  arrangements,   ROS1  arrangements ( P  = .035) and  RET  arrangements ( P  < .001) were identified in younger patients. The frequency of  KRAS   mutations ( P  < .001) was significantly associated with older age at diagnosis and a similar trend existed for  MET  ( P  = .057) but not  BRAF -V600E ( P  = .686) and  ERBB2  ( P  = .083). Additionally, an age at diagnosis of 45 years was found to be a feasible cutoff point to differentiate the younger from the older patients by comprehensive molecular characteristics. These results indicated that younger patients with lung adenocarcinoma were associated with an increased likelihood of harboring a targetable genotype. Distinctive molecular characteristics were identified in patients younger than 45 years with lung adenocarcinoma, which highlights the importance of the NGS assay and personalized therapy in this subpopulation.